Pengaruh Kerjasama tim, Komunikasi Dan Kompetensi Terhadap Kinerja Karyawan PERUMDA Air Minum Bayuangga Kota Probolinggo - Abdur Rosyid; Tumini Tumini; Mutinda Teguh Widayanto (JUMAD : Journal Management, Accounting, & Digital Business, 2023)
This study aims to determine and analyze the effect of teamwork, communication and competence partially and simultaneously on the performance of PERUMDA drinking water bayuangga Probolinggo city employees. This research method is quantitative with a causal associative approach. The research population is all employees of PERUMDA drinking water bayuangga Probolinggo City. The sampling technique uses saturated sampling. The sample in this research is 80 respondents. Source of data used in this research comes from primary data and secondary data. Data was collected using a questionnaire and processed using data analysis methods in the form of validity test, reliability test, classical assumption test, multiple regression analysis, coefficient of determination (R-Square) and hypothesis testing. The results of the study show that teamwork partially has a significant effect on employee performance. And communication partially has a significant effect on employee performance and competence partially has a significant effect on employee performance.